Síntese de uma coleção de cumarinas, possíveis inibidores da enzima acetilcolinesterase - Vieira, Lucas Campos Curcino (Universidade Federal de São Carlos, 2010)
Alzheimer's disease is associated with decreased rates of acetylcholine (ACh) in synaptic process, decreasing the cortical cholinergic transmission, and other neurotransmitters such as norepinephrine, dopamine, serotonin, glutamate and substance P in lesser extension. Some drugs used to treat Alzheimer's disease available in the market are inhibitors of acetylcholinesterase enzyme (AChE). The aim of this work was synthesize and evaluate a library of coumarins with respect to inhibitory activity against AChE in IMERs (Immobilized Enzyme Reactor). This study could contribute to establish the structure-activity relationships and the rational design of possible drugs to treat the Alzheimer's disease. During the development of the project it was used the Knoevenagel condensation between salicyladehydes and diethyl malonate to obtain coumarins. The functionalization of the coumarins had been carried by amidation, nucleophilic substitution, multicomponent and cross coupling reactions. The Suzuki reaction has proved to be an interesting tool to obtain 8-substituted coumarins, a method that has not yet been described in the literature. In total 23 compounds were synthesized. The inhibitory activity of the synthesized compounds was evaluated using Ellman s method adapted to a IMER, which offers the advantage of the stationary phase retains the activity of the enzyme with superior stability and thus it can be used multiple times and in flow. Among the synthesized coumarins, ethyl 2-oxo-7-(2-(piperidin-1- yl)ethoxy)-2H-chromene-3-carboxylate proved to be the best inhibitor for AChE, with an IC50 of 6.3 μM.
Keywords: Síntese orgânica; Cumarinas; Acetilcolinesterase; Química orgânica; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA